Pekatik in gambuh dramatic show - Budiarsa, I Wayan (International journal of linguistics, literature and culture, 2021)
A dramatic performance that presents a play will be found by several figures according to their social status, which is a reflection of people’s lives that are staged on the stage. Gambuh, for example, as the mother of the Balinese drama that appeared afterward and has developed from the Ancient Bali era, Classical Bali to the present, there are at least several strata of characters that appear, one of which is the Pekatik actor. This servant character only appears according to the needs of the storyline being presented, has the character of being innocent, funny, and antawacana using Balinese. Now, in some Gambuh performances, the Pekatik character is very rare because after the 1990s this role was replaced by the Semar character. This study is very important as a source of written data that will be used as reference material for future researchers. This research uses qualitative methods, as well as data collection using literature review techniques, documentation, and interviews.